Positive behavior management in physical activity settings - Lavay, Barry Wayne; French, Ronald W. 1942-; Henderson, Hester (Champaign, IL Human Kinetics, 2016)
It's never been more challenging to manage behavior and motivate students in a physical activity setting. There are more at-risk children and students with disabilities to manage. Physical activity professionals also face the unique challenge of providing instruction to large groups with limited resources and distractions galore. If not handled correctly, these challenges can quickly add up to chaos, ineffective instruction, and frustrated, burnt-out physical activity professionals. That's where the third edition of Positive Behavior Management in Physical Activity Settings, Third Edition comes in. This resource will help you not only overcome those and other discipline challenges, but also use tried-and-true, positive techniques to develop appropriate and responsible behaviors and good character among all learners. This new edition incorporates principles, methods, and instructional practices from psychology, special education, pedagogy, recreation, athletics, and coaching. It shows teachers, coaches, and recreation leaders how to apply the principles that have proven effective in schools, youth sport programs, and recreation sites. -- Publisher's website
Part I Creating a Positive Learning Environment : Chapter 1. Introduction to Behavior Management -- Chapter 2. Preventing Inappropriate Behaviors and Promoting Positive Behaviors -- Part II Exploring Behavior Management Approaches : Chapter 3. The Behavioral Approach: Maintaining and Increasing Behaviors -- Chapter 4. The Behavioral Approach: Redirecting and Decreasing Inappropriate Behaviors -- Chapter 5. The Humanistic Approach: Accepting Social and Personal Responsibility and Building Character -- Chapter 6. The Biophysical Approach: Biological Variables to Behavior -- Chapter 7. Evaluating the Behavioral Intervention -- Part III Behavior Management Challenges : Chapter 8. Bullying of Children and Youth -- Chapter 9. Children and Youth With Unique Needs -- Part IV Behavior Management in Practice : Chapter 10. Behavior Management, Ethics, and Professionalism -- Chapter 11. Steps for Developing a Behavior Management Portfolio
Includes bibliographical references and index.
Keywords: Physical education and training -- Study and teaching; Classroom management; Reinforcement (Psychology).